(untitled) (Baghdad Science Journal, 2018)
In this research, the degradation of Dazomet has been studied by using thermal Fenton process and photo-Fenton processes under UV and lights sun. The optimum values of amounts of the Fenton reagents have been determined (0.07g FeSO4 .7H2O, 3.5µl H2O2) at 25 °C and at pH 7 where the degradation percentages of Dazomet were recorded high. It has been found that solar photo Fenton process was more effective in degradation of Dazomet than photo-Fenton under UV-light and thermal Fenton processes, the percentage of degradation of Dazomet by photo-Fenton under sun light are 88% and 100% at 249 nm and 281 nm respectively, while the percentages of degradation for photo-Fenton under UV-light are 87%, 96% and for thermal Fenton are 70% and 66.8% at 249 nm and 281 nm respectively. In this research the effect of temperature on all the reactions has been studied in the range 25°C-45°C, it has been noticed that the reaction rate constant (k) has increased with increasing temperature, and the best percentage degradation of Dazomet was at 45°C in all processes, so, the thermodynamic functions ?G*, ?H*, ?S* have been calculated